Economic effects of corruption the state trading in Colombia (2013)
The phenomenon of corruption is the scourge in the economy of the countries of the XXI Century, this is immersed in state functions, planning, budgeting, human resource management, management of physical, fiscal control, are the areas, where corruption is presented in the State procurement, especially no transparency or fairness in the bidding process, it is more a monopoly of contractors considered the only ones able to provide products or services to the State, so that are positioned presents dominantly in the contract market of the State.